2016
DOI: 10.1002/adom.201600637
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Enhancement of Ultrathin CuIn1–xGaxSe2 Solar Cells by Nanophotonic Contacts

Abstract: Keywords: ultrathin Cu(In,Ga)Se 2 solar cells, dielectric nanopatterns, light trapping, absorption enhancement, back barrier reduction CuIn 1-x Ga x Se 2 (CIGSe) solar cells have achieved record efficiency values as high as 22.6% for small areas, with module efficiency values near 16.5%. However, for economic viability these values must be achieved with reduced material consumption (especially indium), which requires reducing the CIGSe absorber thickness from 2000-3000 nm to below 500 nm. Softimprinted SiO x n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…Hence, the introduction of the SiO 2 layer changes the rear reflection but compared with the reference some light still exits the solar cell. Light trapping is then needed to take advantage of the rear increased optical reflection, in good agreement with other studies . From these simple measurements, it is hard to find a quantification on the increase of the J sc between the increase in the reflection and the passivation effect.…”
Section: Summary Of the Samples Produced In This Work As Well The Expsupporting
confidence: 68%
See 1 more Smart Citation
“…Hence, the introduction of the SiO 2 layer changes the rear reflection but compared with the reference some light still exits the solar cell. Light trapping is then needed to take advantage of the rear increased optical reflection, in good agreement with other studies . From these simple measurements, it is hard to find a quantification on the increase of the J sc between the increase in the reflection and the passivation effect.…”
Section: Summary Of the Samples Produced In This Work As Well The Expsupporting
confidence: 68%
“…In this work, we expand the study of using photolithography to create a patterned insulator layer with etched features with 700 and 1400 nm which allow to increase the total passivation area while keeping the distance between the contacts the same order of magnitude as the carrier's diffusion length. Furthermore, according to recent studies indicating that SiO 2 is a promising passivation material, we choose to work with that dielectric material …”
Section: Summary Of the Samples Produced In This Work As Well The Expmentioning
confidence: 99%
“…[15][16][17][18] Such passivation layer can lead to three advantageous effects: (i) chemical passivation; (ii) field effect passivation; (iii) increased reflection at the rear contact; all while maintaining good electrical contact and devices with high values of fill factor. While several studies have already shown proof-of-concepts of the point contact structure [17,18,[20][21][22][23][24] and of the passivation properties of Al 2 O 3 , [25][26][27][28][29][30] more detailed studies that analyze the different physical effects involved are needed. Semiconductor surfaces, especially semiconductor-metal interfaces, can host several interface defects, leading to high surface recombination velocities, which in turn lower the electrical performance of solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, Mo was replaced by alternative metals such as W, Ta, or Nb, or dielectrics such as ZrN, Al 2 O 3 , or MgF 2 layers were introduced at the CIGS/Mo interface, and in all cases, improved rear contact reflectance was reported to some degree. In addition, texturing of the rear contact to enhance light trapping was proposed . Thicker absorbers >2 μm were thereby usually only discussed as a limiting case or references.…”
Section: Introductionmentioning
confidence: 99%